Alternatif Bahan Dinding Bata Tanah Putih yang Ditambah Sekam Padi yang Tidak Dibakar - Kristiana Bebhe; Apridus K. Lapenangga (ATRIUM: Jurnal Arsitektur, 2022)
Title: Unburned Rice Husk as an Alternative Additive in the Making of White Soil Brick   Top soil structure in Kupang city and regency consist of  white soil which contain 30-65% sand. This kind of soil is very potential as brick-making material. The experiments carried out turned out that white soil bricks  with rice husks additive without going through the combustion process could reach a compressive strength of 100.9 kg/cm² at a ratio of 1 cement: 7 white soil: 1 rice husk. Without being burned to ashes, rice husks can strengthen white soil bricks. In a previous study, bricks without husk additive with a ratio of 1 cement: 7 white soil with a brick size of 24 x 11 x 6 only reached 51.9 kg/cm² (Bebhe et al., 2020). Meanwhile, in another experiment, white soil brick added with rice husk ash with a size of 23 x 11 x 5 cm could reach 114.3 kg/cm² (Bebhe & Daton, 2021). This proves that rice husks as additive material can increase the compressive strength of white soil bricks .The results of this experiment about compressive strength could exceed the compressive strength of grades 1 and 2 based on SNI 03-0349-1989. For loaded and unprotected wall construction, loaded and protected wall construction, and unencumbered and protected wall construction based on SNI 03-6881.1-2002.   Keywords: white soil brick,  rice husk, compressive strength, wall construction.